Outbreak culture the Ebola crisis and the next epidemic, with a new preface and epilogue - Sabeti, Pardis, 1975- (Harvard University Press, 2021)
A Choice Outstanding Academic Title of the Year "A critical, poignant postmortem of the epidemic." --Washington Post "Forceful and instructive...Sabeti and Salahi uncover competition, sabotage, fear, blame, and disorganization bordering on chaos, features that are seen in just about any lethal epidemic." --Paul Farmer, cofounder of Partners in Health "The central theme of the book...is that common threads of dysfunction run through responses to epidemics...The power of Outbreak Culture is its universality." --Nature "Sabeti and Salahi present a wealth of evidence supporting the imperative that outbreak response must operate in a coordinated, real-time manner." --Science As we saw with the Ebola outbreak--and the disastrous early handling of the COVID-19 coronavirus pandemic--a lack of preparedness, delays, and system-wide problems with the distribution of critical medical supplies can have deadly consequences. Yet after every outbreak, the systems put in place to coordinate emergency responses are generally dismantled. One of America's top biomedical researchers, Dr. Pardis Sabeti, and her Pulitzer Prize-winning collaborator, Lara Salahi, argue that these problems are built into the ecosystem of our emergency responses. With an understanding of the path of disease and insight into political psychology, they show how secrecy, competition, and poor coordination plague nearly every major public health crisis and reveal how much more could be done to safeguard the well-being of caregivers, patients, and vulnerable communities. A work of fearless integrity and unassailable authority, Outbreak Culture seeks to ensure that we make some urgently needed changes before the next pandemic.